Integration and convergence: Lessons from greece's experience in the European Community - G. N. Yannopoulos (Intereconomics, 1985)
The date of entry of Spain and Portugal into the European Community is drawing ever nearer. What are the likely economic consequences of the integration into the EC of these Southern European countries, whose level of development is quite different from that of the other members? The experience of Greece, the first Southern European country to join the EC, can provide some valuable lessons here.
Keywords: 330; Southward Enlargement